1998
DOI: 10.1177/016235329802100206
|View full text |Cite
|
Sign up to set email alerts
|

Children's Thoughts about the Future: Comparing Gifted & Nongifted Students after 20 Years

Abstract: Twenty years after the original study comparing gifted and regular students' thoughts and concerns about the future, this study réexamines those same issues in the same school community. In 1975, gifted students were significantly more pessimistic toward the future than regular students. When faced with future problems, the gifted students were significantly more solutions oriented than regular students. Today, the situation has changed. Both groups are increasingly more negative toward the future, and the pes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 5 publications
0
9
0
4
Order By: Relevance
“…Bazı araştırmacılar üstün zekâlı öğrencilerin gelecekle ilgili kötümser olduklarını bulmuştur (George ve Gallagher, 1973;Landua, 1976). Fakat üstün zekâlı öğrenciler diğer akranlarına göre daha fazla çözüme yöneliktirler (George & Scheft, 1998). Bununla birlikte üstün zekalı kız ve erkeklerin gelecekle ilgili farklı beklentileri olduğu belirtilmektedir (Callahan, Cunnigham, ve Plucker, 1994;Schuler, 1999).…”
Section: Geni̇şleti̇lmi̇ş öZetunclassified
See 1 more Smart Citation
“…Bazı araştırmacılar üstün zekâlı öğrencilerin gelecekle ilgili kötümser olduklarını bulmuştur (George ve Gallagher, 1973;Landua, 1976). Fakat üstün zekâlı öğrenciler diğer akranlarına göre daha fazla çözüme yöneliktirler (George & Scheft, 1998). Bununla birlikte üstün zekalı kız ve erkeklerin gelecekle ilgili farklı beklentileri olduğu belirtilmektedir (Callahan, Cunnigham, ve Plucker, 1994;Schuler, 1999).…”
Section: Geni̇şleti̇lmi̇ş öZetunclassified
“…In addition, they analyzed students' attitudes when faced with future problems. According to the analysis, the gifted students were significantly more solution-oriented than non-gifted students (George & Scheft, 1998). In 1998, a similar study revealed that both gifted and non-gifted groups were becoming increasingly more negative towards the future, and the pessimism of gifted students has dramatically increased.…”
Section: Introductionmentioning
confidence: 96%
“…For most of the children, grades were obtained in reading, science, social studies, language arts, and mathematics." (Ramsay & Richards, 1997, p. 162) Baker (1996; Gallucci, Middleton, and Kline (1999); George and Scheft (1998); Hannah and Shore (1995); Hunt (1996); Jausovec (1996); Jausovec (1997); Jin, Kim, Park, and Lee (2007); Jin, Kwon, Jeong, Kwon, and Shin (2006); Nikolova and Taylor (2003); Ostatnikova, Putz, Celec, Okkelova, and Laznibatova (2006); Parker and Mills (1996); Ramsay and Richards (1997); Shavinina and Kholodnaja (1996); Van Garderen and Montague (2003) Another commonly used method for identifying gifted individuals was achievement test scores. Thirty-two articles reported the use of achievement test scores as a criterion for participant selection.…”
Section: Resultsmentioning
confidence: 99%
“…1) Ackerman (1997);Bain and Bell (2004);Baker (1996); L. K. S Chan (1996)Delcourt, Lyn, and Rejskind (1997);Gallucci et al (1999);Gaultney (1998);Gentry, Gable, and Springer (2000);George and Scheft (1998);Hannah and Shore (1995);Hawkins (1997);Heng (2000);Kher-durlabhji et al (1997);Klein and Zehms (1996);Liu et al (2008);McCoach and Siegle (2002); Mendez(2000);Merrell et al (1996);Mooij and Driessen (2008);Muj, Yeung, Low, and Jin (2000);Nail and Evans (1997);Parker and Mills (1996);Rigo et al (1998);Schapiro, Schneider, Shore, Margison, and Udvari (2009);Schommer and Walker (1997);…”
mentioning
confidence: 99%
“…In addition, gifted students' problems can be further exacerbated by the unique issues and challenges that they might encounter in their family and school environments and by their own personal characteristics. George and Scheft (1998) suggested that, in order to increase gifted students' optimism and decrease their pessimism, in the curricula, "genuinely complex, futuristic problems should be included as early as the elementary grades, and gifted children should be challenged to grapple with these problems" (p. 237). Optimism can be enhanced for the gifted students, and schools and parents should encourage this to happen.…”
Section: Discussionmentioning
confidence: 99%